2020
DOI: 10.3892/mmr.2020.11422
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of RAGE and glucose‑induced inflammation in bone marrow mesenchymal stem cells: Effect and mechanism of action

Abstract: The occurrence and development of hyperglycemia-induced inflammation is associated with increased expression of receptor for advanced glycation end products (RAGE) and inflammatory factors, including IL-1β, TnF-α and il-6. Previous studies have reported that the nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome interacts with thioredoxin-interacting protein (TXNIP) and serves a crucial role in inflammation. FPS-ZM1 has been identified as target inhibitor of RAGE and has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…Accordingly, small-molecular inhibitors such as TTP488, FPS-ZM1, etc. targeting RAGE and its intracellular signaling pathway have been developed (66,67). These small molecule inhibitors hold great promise for the treatment of multiple metabolic bone diseases and merit further investigation.…”
Section: Glycation End-productmentioning
confidence: 99%
“…Accordingly, small-molecular inhibitors such as TTP488, FPS-ZM1, etc. targeting RAGE and its intracellular signaling pathway have been developed (66,67). These small molecule inhibitors hold great promise for the treatment of multiple metabolic bone diseases and merit further investigation.…”
Section: Glycation End-productmentioning
confidence: 99%
“…HG-induced EPC dysfunction by activating TXNIP-NLRP3 in ammasome pathway through sthe formation of AGEs [71,72], and the RAGE-TXNIP pathway has also been shown to play a crucial role in a variety of cellular functional impairments [73][74][75]. Therefore, our results concluded that HG activated the RAGE-TXNIP-NLRP3 in ammasome pathway through the formation of AGEs.…”
Section: Caspase-1mediates Cat Inactivationmentioning
confidence: 51%
“…In contrast, in MSCs, RAGE is induced and activated by HMGB1 to promote the expression of CXCR4, 57 TGFβ, and proinflammatory cytokines. 58 , 59 However, reports analyzing the modification of HMGB1 and its function in MSCs are scarce. The differential action of the oxidized and reduced forms in this study may be important for future targeting of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, oxidized HMGB1 was considered to be a highly functional ligand for RAGE in cancer. In contrast, in MSCs, RAGE is induced and activated by HMGB1 to promote the expression of CXCR4, 57 TGFβ, and proinflammatory cytokines 58,59 . However, reports analyzing the modification of HMGB1 and its function in MSCs are scarce.…”
Section: Discussionmentioning
confidence: 99%